Pengembangan Buku Saku IPA Terpadu Berbasis Learning Cycle Pada Materi Sistem Organisasi Kehidupan Untuk Siswa Kelas VII SMP/MTs - Sri Kustanti; Leni Marlina; Eko Wulandari (BIOCOLONY, 2021)
This research is motivated by limited textbooks integrated science used by students in the learning process. This study aims to describe the prosess of developing an integrated science pocket book based on Learning cycle on material life organization system for seventh grade students of SMP/MTs which is valid and practical. Type of research is development research using the 4-D menthod which inclueds the stage an integrated science pocket book based Learning cycle was only carried out until the dissemination stage was limited to teacher. The subjects of this study consisted of 7 (seven) validators and practicality test was carried out by 2 teachers, then this data was analyzed by descriptive analysis. Based on the results of the reasearch, the product is pocket book. The pocket book was declared very valid and practical. The validator both from the aspects of the feasibility of content, language, presentation and graphics with a validity value of 95%. It’s means on very practical category. The pocket book produced was also deemed practical by the teacher in terms of ease of use, learning time, and attractiveness with an average value of 3.45. The concluded of research is the pocket book has been declared valid and practical.